Experimental and numerical investigation of cyclic response of a glass curtain wall for seismic performance assessment. (30th October 2018) - Aiello, Carolina; Caterino, Nicola; Maddaloni, Giuseppe; Bonati, Antonio; Franco, Annalisa; Occhiuzzi, Antonio
Highlights: One among the few glass facade experimental campaigns worldwide realized till now. An innovative machine adopted for the first time in occasion of performed tests. Interesting results are discussed in terms of experimental and numerical outcomes. Abstract: In contemporary architecture, the use of the glass curtain walls is increasingly growing. However, after experiencing earthquake motions, they have sometime shown damage, which might cause considerable life-safety hazards for pedestrian and occupants of buildings, as well as significant economic losses to owners, due to downtime and cost for repairing. This work aims to investigate the behaviour of such systems under seismic loads, so to contribute to the enhancement of the capability of designers and manufacturers in dealing with seismic vulnerability of glazed systems and reducing earthquake induced losses. This study shows cyclic experimental tests performed at the Construction Technologies Institute (ITC) of the Italian National Research Council (CNR) for seismic performance assessment of a full-scale aluminium-glass façade, designed and manufactured according to a standard technology for the European market. A non-linear finite element model has been calibrated according to experimental results. The aim is understanding further aspects of the lateral behaviour of these non-structural elements and also giving useful information for numerical simulations of similar façades, that in the next future should be performed even in the absence of experimental data.